Effects of combined weight and chain versus combined weight and elastic band training on body composition, muscular strength and endurance among untrained males in Iran - Kashiani, Amir Bahram (2018)
Several studies have shown a positive association between variable resistance training and improvement of body composition and muscular performance. However, the most effective method of variable resistance training to improve body composition and muscular performance in untrained individuals remains unclear. The objective of this study was to examine the effects of two methods of variable resistance training on body composition, maximal muscular strength and endurance among untrained male adults. Fifty healthy untrained males (age: 21.5 ± 1.95 years old) were selected randomly and assigned into three groups: combined weight and chain (WC), combined weight and elastic band (WE), and free-weight (CG). All three groups completed 24 weeks of upper and lower body high intensity resistance training (70-90% of one-repetition maximum) with three-four sets for two-three times per week. Approximately 65% of the resistance was provided by free-weights and 35% of the resistance was provided by chains and elastic bands (assessed at the top of the range of motion) for the WC and WE groups, respectively. Depended variables involving body composition, maximal muscular strength and maximal muscular endurance using bioelectrical impedance analyser, one-repetition maximum, and maximum repetitions to muscular fatigue were measured, respectively in pre-test, post-test 1 (week 6), post-test 2 (week 12), post-test 3 (week 18) and post-test 4 (week 24). Significance level was set at P < 0.05. No differences existed among all groups at baseline for depended variables. A mixed model ANOVA with repeated measurements analysis revealed that body fat mass (FM) and body fat free mass (FFM) decreased and increased, respectively significantly from pre-test values in all groups (P = 0.001), but there were no differences in FM and FFM among the groups (P = 0.23 and P = 0.35, respectively). In the WE and WC groups, maximal muscular strength and endurance were significantly greater than CG group during and after the intervention. Finally, in the WE group, maximal muscular strength were significantly greater than WC group only in post-test 4 (chest press: 56.02 ± 3.3 vs. 52.64 ± 4.9 kg, overhead press: 41.91 ± 2.8 vs. 38.23 ± 3 kg, and squat: 104.26 ± 6.2 vs. 96.47 ± 6.6 kg), and maximal muscular endurance were significantly greater in the WE group compared to the WC group in post-tests 3 and 4 (Post-test 3 = chest press: 18.58 ± 1.2 vs. 16.64 ± 1.5 repetitions, overhead press: 15.82 ± 0.9 vs. 14.52 ± 1 repetitions, and squat: 20.05 ± 0.8 vs. 18.11 ± 1.6 repetitions. Post-test 4 = chest press: 20.47 ± 1.5 vs. 17.82 ± 1.5 repetitions, overhead press: 17.58 ± 1.1 vs. 15.52 ± 1.1 repetitions, and squat: 21.82 ± 0.9 vs. 19.29 ± 1.4 repetitions). The results of this study show that variable resistance training has a slightly better effect than free weight to improve body composition, in particular, WE variable resistance training has a better effect significantly to improve upper and lower body muscular strength and endurance during and after 24 weeks of variable resistance training among untrained male adults in Iran.